2006
DOI: 10.1261/rna.58806
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 associates with telomere ends and stimulates telomerase activity

Abstract: Telomerase is a ribonucleoprotein enzyme complex that reverse-transcribes an integral RNA template to add short DNA repeats to the 39-ends of telomeres. G-quadruplex structure in a DNA substrate can block its extension by telomerase. We have found that hnRNP A1-which was previously implicated in telomere length regulation-binds to both single-stranded and structured human telomeric repeats, and in the latter case, it disrupts their higher-order structure. Using an in vitro telomerase assay, we observed that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
149
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 50 publications
10
149
0
Order By: Relevance
“…In another role that is likely significant in cancer, human A1 has been implicated in lengthening and maintaining telomeres, a function that is conserved in C. elegans and possibly yeast (Lin and Zakian 1994;LaBranche et al 1998;Joeng et al 2004). A1 binds to the single-stranded telomeric DNA repeat sequence TAGGGT (a sequence almost identical to the high-affinity SELEXbinding site identified for A1 using RNA), where it is capable of stimulating telomerase activity (Burd and Dreyfuss 1994;Zhang et al 2006). A similar function has been shown for hnRNP A2 (Kamma et al 2001).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 77%
“…In another role that is likely significant in cancer, human A1 has been implicated in lengthening and maintaining telomeres, a function that is conserved in C. elegans and possibly yeast (Lin and Zakian 1994;LaBranche et al 1998;Joeng et al 2004). A1 binds to the single-stranded telomeric DNA repeat sequence TAGGGT (a sequence almost identical to the high-affinity SELEXbinding site identified for A1 using RNA), where it is capable of stimulating telomerase activity (Burd and Dreyfuss 1994;Zhang et al 2006). A similar function has been shown for hnRNP A2 (Kamma et al 2001).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 77%
“…In particular, hnRNP A1, A2B1, A3, D and E can associate with the single-stranded telomeric repeats, although only hnRNP A1 has been shown to infl uence telomere length 11 -13 (reviewed in Ford et al 14 ). Th e hnRNP A1, D and C1 / C2 are also able to interact with human telomerase 12,15 -18 and hnRNP A1 and D can unwind G-quadruplexes 18,20 . Th e hnRNP interaction with TERRA transcripts and the eff ects on TERRA and telomeres that we described here further support a central role of hnRNPs in telomere biology.…”
Section: Discussionmentioning
confidence: 99%
“…Th e hnRNP proteins can also aff ect chromatin remodelling and transcription in a DNA-independent manner through protein -protein interactions (for example, hnRNP U binds RNA polymerase II) (reviewed in Carpenter et al 19 ). Th e hnRNP A1 and D have been also implicated in transcription owing to their ability to bind to and unwind G-quadruplexes 18,20 . A role for hnRNP A1 in transcription that does not involve unwinding of G-quadruplexes has been also reported 21 .…”
mentioning
confidence: 99%
“…6, 7 and 8). Human hnRNP A1 is a single-stranded nucleic acidbinding protein, which has many functions in various aspects of mRNA maturation and in telomere length regulation [20,21]. On the other hand, Murzin et al have observed a novel folding motif in four different proteins, which bind oligonucleotides or oligosaccharides: in nuclease, anticodon binding domain of asp-tRNA synthetase and B-subunits of heat-labile enterotoxin and verotoxin-1 (in some enzymes and toxins) [22].…”
Section: Discussionmentioning
confidence: 99%